Newman and Carranza's Clinical Periodontology and Implantology - Newman, Michael G.; Klokkevold, Perry R.; Elangovan, Satheesh; Hernandez-Kapila, Yvonne L.; Carranza, Fermin A.; Takei, Henry H., 1938- (St. Louis, Missouri : Elsevier, 2024)
"Learn and master a range of clinical techniques and achieve therapeutic goals with Newman and Carranza's Clinical Periodontology and Implantology, 14th Edition! Unmatched for its comprehensive approach, this resource provides detailed, up-to-date information on the etiology and pathogenesis of periodontal disease. Basic and advanced evidence-based information on the various treatment modalities employed in periodontics and implantology is presented in an easy-to-read format, with callout boxes throughout the text highlighting the clinical relevance of foundational basic science information. Full-color photos and radiographic images depict periodontal conditions and procedures, and the Atlas of Periodontal Pathology is one of the most comprehensive ever compiled in a periodontal textbook. Written by a team of leading experts led by Michael G. Newman, this text not only demonstrates how to perform periodontal procedures but explains the evidence supporting each treatment and provides knowledge on how to achieve the best possible outcomes of periodontal therapy and implant treatment. An eBook version is included with print purchase, providing access to all the text, figures, and references, plus the ability to search, customize content, make notes and highlights, and have content read aloud. The eBook version included with print purchase also includes Periopixel 3D color illustrations, a periodontal classification calculator and interactive learning tool, review questions, case studies, videos, 3D animations, and more! This edition features new chapters on Precision Medicine, Pocket Reduction Therapy, Periodontal Referral, and Digital Implant Workflows, as well as an updated glossary of terms linked to the eBook. It also features first-of-its-kind content on the effects of COVID-19 on treatment from key opinion leaders in this area. Case studies reflect the new format of the Integrated National Board Dental Exam (INBDE)."--
Clinical Periodontology and Implantology in the Era of Precision Medicine -- Evidence-Based Decision Making -- Critical Thinking: Assessing Evidence -- Anatomy, Structure, and Function of the Periodontium -- Classification of Diseases and Conditions Affecting the Periodontium -- Fundamentals in the Methods of Periodontal Disease Epidemiology -- Atlas of Periodontal Diseases -- Periodontal Disease Pathogenesis -- Precision Dentistry: Genetics and Epigenetics of Periodontitis -- Biofilm and Periodontal Microbiology -- Host-Microbe Interactions and the Inflammatory Response -- Resolution of Inflammation -- Aging and the Periodontium -- Defense Mechanisms of the Gingiva -- Dental Biofilm-Induced Gingivitis and Its Management -- Select Systemic and Local Diseases That Affect the Gingiva -- Acute Gingival Infections and Management -- Desquamative Gingivitis -- Gingival Enlargement and Management -- Periodontal Health and Disease in Children and Adolescents -- Periodontitis -- The Periodontal Pocket Formation and Patterns of Bone Loss -- Risk Factors of Periodontal Disease (Smoking) -- The Role of Dental Calculus and Other Local Predisposing Factors -- Influence of Systemic Conditions on the Periodontium -- Impact of Periodontal Infection on Systemic Health -- Pathology and Management of Periodontal Problems Associated With Viral Infection, Including HIV, COVID, and Others -- Periodontal Therapy in the Female Patient -- Aging and Periodontal Health: A Long-Term Relationship -- Acute Periodontal Infections and Management -- Halitosis (Breath Malodor) -- Periodontal Response to External Forces -- Sleep-Related Breathing Disorders -- Masticatory System Disorders That Influence the Periodontium -- Role of Occlusion and TMD in Periodontal Disease Management -- Levels of Clinical Significance -- Electronic Dental Records and the Role of Health Information Technology in Dentistry -- Periodontal Examination -- Radiographic Aids in the Diagnosis of Periodontal Disease -- Periodontal Risk Assessment -- Determination of Prognosis -- Periodontal Treatment Plan -- Nonsurgical Phase of Periodontal Therapy -- Clinical Practice Guideline for Treatment of Periodontitis -- Restorative Interrelationships -- Multidisciplinary Versus Interdisciplinary Approaches to Dental and Periodontal Problems -- Periodontal Referral -- Orthodontics in Periodontal Therapy -- Endo-Perio Lesions -- Plaque Biofilm Control for the Periodontal Patient -- Sonic and Ultrasonic Instrumentation and Irrigation -- Chemotherapy: Use of Systemic Antibiotics -- Locally Delivered, Controlled-Release Antimicrobials -- Host Modulation -- Surgical Phase of Periodontal Therapy -- Surgical Training and Technology -- Sedation in Periodontics and Implant Surgery -- Periodontal and Peri-Implant Surgical Anatomy -- General Principles of Periodontal Surgery -- Periodontal Surgical Therapy -- Pocket Reduction Therapy-Resective Approach -- Periodontal Regeneration -- Lasers in Periodontal and Peri-Implant Therapy -- Periodontal Plastic and Esthetic Surgery -- Preparation of the Periodontium for Restorative Dentistry -- Periodontal Treatment of Medically Complex Patients -- Periodontal Microsurgery -- Diagnosis and Management of Periodontal Abscesses -- Supportive Periodontal Treatment -- Results of Periodontal Treatment -- Integrating Implants With Periodontal Therapy -- Peri-Implant Anatomy, Biology, and Function -- Clinical Evaluation of the Implant Patient -- Diagnostic Imaging for the Implant Patient -- Prosthetic Considerations: Partially Edentulous -- Prosthetic Considerations: Fully Edentulous -- Basic Implant Surgical Procedures -- Advanced Implant Surgical Procedures: Horizontal and Vertical Augmentation -- Advanced Implant Surgical Procedures: Maxillary Sinus Augmentation -- Advanced Surgical Procedures: Simultaneous Implant Placement and Tissue Augmentation in the Esthetic Zone -- Dental Implant Microsurgery: Immediate Placement -- Piezoelectric Bone Surgery -- Digitally Assisted Implant Placement Surgery -- From Implant Placement to Provisional Restoration -- Complications in Dental Implantology -- Supportive Implant Treatment -- Results of Implant Treatment
Includes bibliographical references and index.
Keywords: Periodontal Diseases; Periodontics; Dental Hygienists; Oral Surgical Procedures